2022
DOI: 10.3389/fcvm.2022.981012
|View full text |Cite
|
Sign up to set email alerts
|

First in-human quantitative plaque characterization with ultra-high resolution coronary photon-counting CT angiography

Abstract: PurposeTo assess the effect of ultra-high-resolution coronary CT angiography (CCTA) with photon-counting detector (PCD) CT on quantitative coronary plaque characterization.Materials and methodsIn this IRB-approved study, 22 plaques of 20 patients (7 women; mean age 77 ± 8 years, mean body mass index 26.1 ± 3.6 kg/m2) undergoing electrocardiography (ECG)-gated ultra-high-resolution CCTA with PCD-CT were included. Images were reconstructed with a smooth (Bv40) and a sharp (Bv64) vascular kernel, with quantum ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…The latter study even demonstrated 40% less noise for PCD-CT UHR-based temporal bone imaging as compared to comb-filter UHR EID-CT imaging at matching radiation doses and reconstruction settings. 33 A variety of further studies have been published on HR and UHR PCD-CT imaging highlighting its value for lung assessment, 15,25,27,[34][35][36][37][38][39] cardiac imaging 20,24,[40][41][42][43][44] and musculoskeletal applications. 19,33,[45][46][47][48] UHR imaging is of particular interest for these anatomical areas because the clear depiction of fine details may effectively enhance diagnostic accuracy.…”
Section: Translating the Benefits Of Pcd-ct Into Clinical Routine Imp...mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter study even demonstrated 40% less noise for PCD-CT UHR-based temporal bone imaging as compared to comb-filter UHR EID-CT imaging at matching radiation doses and reconstruction settings. 33 A variety of further studies have been published on HR and UHR PCD-CT imaging highlighting its value for lung assessment, 15,25,27,[34][35][36][37][38][39] cardiac imaging 20,24,[40][41][42][43][44] and musculoskeletal applications. 19,33,[45][46][47][48] UHR imaging is of particular interest for these anatomical areas because the clear depiction of fine details may effectively enhance diagnostic accuracy.…”
Section: Translating the Benefits Of Pcd-ct Into Clinical Routine Imp...mentioning
confidence: 99%
“…24,40 Two recent studies assessing the UHR scan mode of clinical PCD-CT in patients referred for coronary CT angiography have shown that coronary arteries can be visualized in excellent quality with improved visualization of non-calcified plaque components and with reduced blooming of calcified plaques. 43,44 For bone imaging, fine bone details and previously occult hairline fractures may become apparent. 33,46,49,50 In a clinical feasibility study including 32 patients who underwent both UHR PCD-CT imaging on a prototype CT system with optimized reconstruction settings and standard-of-care EID-CT imaging, Baffour et al reported improved visualization of osseous structures of the pelvis and shoulder for UHR PCD-CT imaging at a 31-47% lower radiation dose.…”
Section: Translating the Benefits Of Pcd-ct Into Clinical Routine Imp...mentioning
confidence: 99%
“…In general, diagnostic confidence will increase with PCD-CT compared with EID-CT in terms of coronary calcifications, calcification sharpness, and calcification conspicuity, but also noncalcified plaque conspicuity. 5,26 However, a systematic evaluation of the PureLumen technique against an invasive reference standard (ie, catheter angiography) is still missing and must be subject of future studies.…”
Section: Purelumenmentioning
confidence: 99%
“…Photon-counting detector CT enables higher spatial resolution in comparison with conventional EIDs. Photon-counting detector CT scanners can be manufactured with smaller detector elements that do not contain separate scintillator elements and reflecting septa, generating pixel sizes ranging from 0.225 to 0.5 mm at the detector, contrasting pixel sizes in the order of 1 mm created by EIDs 40–42 . The advances in spatial resolution may be translated to clinical applications for visualization of very fine anatomic superstructures that extend beyond the current resolution capacities of state-of-the-art EIDs.…”
Section: Clinical Applicationsmentioning
confidence: 99%